Naprężenie w Sprężysto-Plastycznej Kuli z Pustka Kulistą, Znajdującej się w Zmiennym Polu Temperatur - Raniecki, B. (Engineering Transactions, 1966)
The stress (instantaneous and final) in the body under consideration is produced by a heating- cooling process at the outer surface of the body. Assuming linear strain-hardening, the influence of the temperature on the physical properties of the material is disregarded. The problem is considered to be quasi-static. The determination of the borders between time-variable regions in the material is reduced to the solution of a set of equations, one of which is an ordinary differential equation of the 1-st order and the other – a functional equation. The solution for the full spherical bodyis obtained as a particular case.